Ta‘līq Surat Luqmān dalam Manuskrip Tafsir Jalālain Kyai Bakri Kajoran Magelang: Etika dan Humanisme Perspektif Pribumisasi Islam Abdurrahman Wahid - Rojab, Bengawan; Saifudin, Ahmad; Rosowulan, Titis (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Amidst the whirlwind of social change and the rapid pace of globalization, Islamic boarding schools in the archipelago preserve an intellectual heritage that has stood the test of time. One such legacy is found in the Tafsir Jalālain manuscript by Kyai Bakri Kajoran. The ta‘līq commentary on Surat Luqmān is more than a marginal note; it is a profound reflection on ethics and humanity, grounded in the realities of Javanese society. Each line of commentary fosters a dialogue between the sacred text and lived experience, linking the values of tawhid, gratitude, and filial piety with the moral challenges of the colonial era. Through a qualitative content analysis of seventy-three commentaries, this study explores how Kyai Bakri blends universal Islamic teachings with local wisdom. This makes the manuscript a space for the dialectic between tradition and the needs of the times, not merely an exegesis. Based on Abdurrahman Wahid’s theory of the indigenization of Islam, the study concludes that these ta‘līqs bridge the gap between the Qur'an's message and the social context of Javanese society, thereby strengthening the ethical and humanistic dimensions of pesantren education. This finding underscores the importance of preserving manuscripts by Nusantara scholars as a source of inspiration for developing inclusive, contextual, and transformative Islamic thought.